2013
DOI: 10.1128/aem.02454-13
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of Heavy Metal Ion Sorption to Cell-Extracellular Polymeric Substance-Mineral Aggregates by Using Metal-Selective Fluorescent Probes and Confocal Laser Scanning Microscopy

Abstract: b Biofilms, organic matter, iron/aluminum oxides, and clay minerals bind toxic heavy metal ions and control their fate and bioavailability in the environment. The spatial relationship of metal ions to biomacromolecules such as extracellular polymeric substances (EPS) in biofilms with microbial cells and biogenic minerals is complex and occurs at the micro-and submicrometer scale. Here, we review the application of highly selective and sensitive metal fluorescent probes for confocal laser scanning microscopy (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 100 publications
1
48
0
Order By: Relevance
“…4E to H), seem to originate from a thin, electron-dense, and nanometer-size grained mineral layer at the outer rim of the EPS capsule. The organic EPS polymers likely block kinks and steps of the initially formed mineral nuclei and thus prevent the formation of larger crystals within the EPS layer (55). We indeed observed that the minerals within the capsule, visible as filamentous structures, were generally much smaller grained than those on the surface.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…4E to H), seem to originate from a thin, electron-dense, and nanometer-size grained mineral layer at the outer rim of the EPS capsule. The organic EPS polymers likely block kinks and steps of the initially formed mineral nuclei and thus prevent the formation of larger crystals within the EPS layer (55). We indeed observed that the minerals within the capsule, visible as filamentous structures, were generally much smaller grained than those on the surface.…”
Section: Discussionmentioning
confidence: 49%
“…In the case of BoFeN1, the Fe(III) mineral precipitation starts in the periplasm, continues on the cell surface, and then terminates in the cytoplasm (13). In all cultures, mineral precipitation at the cell surface was probably initially avoided by a protective EPS layer surrounding the cells, which potentially complexed Fe(III) and/or inhibited crystal nucleation and crystal growth because of binding of Fe ions by the organics (55). When nitrite diffuses through this EPS layer, green rust and goethite minerals form on the outside of the EPS layer, catalyzing Fe(II) oxidation and Fe(III) mineral formation (31,46,69).…”
Section: Discussionmentioning
confidence: 99%
“…In order to know whether iron can bind to Psl under physiological conditions, particularly in biofilms, we applied a highly selective and sensitive iron-specific fluorescent probe to label iron and to detect the localization of iron in the Psl matrix of P. aeruginosa biofilms (58). Biofilms after 1 day of growth under iron-replete (100 M) or iron-limiting (2 M) conditions were stained by Psl-staining lectin HHA-FITC (green fluorescence) and an ironspecific fluorescent probe (red fluorescence).…”
Section: Resultsmentioning
confidence: 99%
“…Fe(III) minerals similar to ferrihydrite precipitate in isotopic equilibrium with Fe(II/III) interm . soluble based on binding with a fluorescent sensor that does not bind to Fe(III) in minerals (Hao et al, 2013;Wu et al, 2014). This phase was co-localized to EPS, organics excreted by bacteria into their surroundings, based on the spatial overlap of fluorescence from a fluorescent Fe(III)-sensor and a fluorescent dye that binds EPS in confocal laser scanning microscopy (CLSM) images.…”
Section: Mineralogical Transformations Occurring During Fe(ii) Oxidatmentioning
confidence: 99%